2022
DOI: 10.1088/1748-605x/ac61f9
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional culture and chondrogenic differentiation of mesenchymal stem cells in interconnected collagen scaffolds

Abstract: Interconnected scaffolds are useful for promoting the chondrogenic differentiation of stem cells. Collagen scaffolds with interconnected pore structures were fabricated with poly(lactic acid-co-glycolic acid) (PLGA) sponge templates. The PLGA-templated collagen scaffolds were used to culture human bone marrow-derived mesenchymal stem cells (hMSCs) to investigate their promotive effect on the chondrogenic differentiation of hMSCs. The cells adhered to the scaffolds with a homogeneous distribution and proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…However, 2D culture cannot simulate the practical physiological conditions of stem cells niche and this severely limits the therapeutic efficacy and impedes the clinical translation of stem cells-based therapy. 3D culture system can mimic a more actual cellular physiological condition through the elaborate interactions of cell to cell and cell to extracellular matrix [ 17 , 22 , 23 ]. In addition, previous studies have indicated that 3D cultured MSCs possessed enhanced stemness and improved therapeutic effects [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, 2D culture cannot simulate the practical physiological conditions of stem cells niche and this severely limits the therapeutic efficacy and impedes the clinical translation of stem cells-based therapy. 3D culture system can mimic a more actual cellular physiological condition through the elaborate interactions of cell to cell and cell to extracellular matrix [ 17 , 22 , 23 ]. In addition, previous studies have indicated that 3D cultured MSCs possessed enhanced stemness and improved therapeutic effects [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…3D culture system can mimic a more actual cellular physiological condition through the elaborate interactions of cell to cell and cell to extracellular matrix [ 17 , 22 , 23 ]. In addition, previous studies have indicated that 3D cultured MSCs possessed enhanced stemness and improved therapeutic effects [ 22 , 23 ]. Therefore, it is instructive to maintain the physiological features of CPCs and maximize the efficacy of CPCs by using 3D culture system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After reverse transcription with a high-capacity cDNA reverse transcription kit, amplification of glyceraldehyde-3-phosphate dehydrogenase (GAPDH, a housekeeping gene), collagen I (Col1a2), collagen II (Col2a1), aggrecan (Acan), and SOX9 was conducted with a QuantStudio ® 3 Real-Time PCR System (Thermo Fisher Scientific). The previously reported primer and probe sequences as shown below were used [ 52 , 53 ]. GAPDH: (forward) 5′-ATGGGGAAGGTGAAGGTCG-3′, (reverse) 5′-TAAAAGCAGCCCTGGTGACC-3′, (probe) 5′-CGCCCAATACGACCAAATCCGTTGAC-3′; Col1a2: (forward) 5′-CAGCCGCTTCACCTACAGC-3′, (reverse): 5′-TTTTGTATTCAATCACTGTCTTGCC-3′, (probe): 5′−CCGGTGTGACTCGTGCAGCCATC-3′; Col2a1: (forward) 5′GGCAATAGCAGGTTCACGTACA-3′, (reverse) 5′-CGATAACAGTCTTGCCCCACTT-3′, (probe) 5′−CCGGTATGTTTCGTGCAGCCATCCT-3′; Acan: (forward) 5′-TCGAGGACAGCGAGGCC-3′, (reverse) 5′-TCGAGGGTGTAGCGTGTAGAGA-3′, (probe) 5′-ATGGAACACGATGCCTTTCACCACGA-3′; SOX9: (forward) 5′-CACACAGCTCACTCGACCTTG-3′, (reverse) 5′-TTCGGTTATTTTTAGGATCATCTCG-3′, (probe) 5′-CCCACGAAGGGCGACGATGG-3′.…”
Section: Methodsmentioning
confidence: 99%